Diagnosing cancer in general practice: when is cancer suspected?. Issue 6541 (26th July 1986) - Nylenna, M
Abstract : Of 10, 278 encounters with patients recorded by 33 general practitioners in a defined Norwegian population during a two month period, 429 (4.2%) were classified as resulting in a follow up for suspected cancer. The patient's fear of cancer was the most important indicator of suspicion of cancer among the doctors. Patients who consulted for digestive and gynaecological problems were most frequently suspected of having cancer. Comparing the pattern of suspicion of cancer with the incidence of cancer in the area showed a relative oversuspicion in young patients and women.